Simultaneous Detection of the Ipn and Isa Viruses in Outbreaks of Clinical Disease and Mortality in Farmed Atlantic Salmon, Salmo Salar L., in Chile - Spencer-Ossa, E; Sandino-Garcia, A; Rivas-Aravena, A; Cortez-San Martin, M (2012)
Sin Editorial Disponible